Endline Assessment : Improving Birth Registration Using the Existing Community Structures and Immunization Processes - Hailemariam, Getahun (World Bank, Washington, DC, 2019)
This report summarizes key findings from the endline assessment of the pilot project, Improving Birth Registration Using Existing Community Structures and Immunization Processes. The project was undertaken in Yilmana Densa and Goji Qolela woredas (districts); Hintalo Wajirat and Enderta woredas; and Amibara and Awash Fentale woredas, which are the intervention and control woredas in Amhara, Tigray, and Afar regions, respectively. The overall objective was to enhance a well-functioning civil registration and vital statistics (CRVS) system by integrating community health structures with civil status offices. This assessment was quasi-experimental by design and used longitudinal data, supplemented by a methodology like the one used in the baseline survey to compare improvements in key variables. The assessment compared intervention and control groups, with measuring use of civil registration services, and compared the outcome of the CRVS service provision in terms of improvement. The assessment used qualitative and quantitative methods of data collection and analysis. Some of the key findings of the assessment include: After introduction of the project, the rate of births registered within 90 days increased from the previous year and was greater than in the control woredas; CSOs in the intervention areas regularly visited communities for awareness creation and motivation and for registration when the WDA invited them; qualitative data from KIIs and FGDs generally indicate that the large increase in birth registration in Afar was the result of the presence of CSOs at the kebele level, community mobilization, and no civil status office staff turnover during the project; the community consistently reviewed the registration progress monthly, identifying challenges faced and ways forward at the kebele level, and noted this in the minutes.